The process of Peruvian independence and constitutionalism in the formation of the republic: the contribution of the invisible - Santos Gomero, Walber José (2024)
The study presents the results of a bibliographic review on constitutionalism that was established after the war of independence and that was assumed by the Constituent Congress of 1822. From the perspective of the historiography of law with an interdisciplinary approach, it is proposed a valuation of the role and contribution of women, peasants and Afro-descendants to the political independence of our country. From this, it can be affirmed that the founding of the republic was the product of a complex socio-political process, and that the official and patriarchal history has made invisible the other protagonists, the population sectors historically excluded from the political, legal, economic and constitutional of said Constituent Congress. Thus, it is intended to contribute to the understanding, analysis and critical assessment of the role and contribution of the feminist, peasant and Afro-Peruvian movement in the forging of a Constitutional State of Law and a Republic of equals. It concludes by raising the question of how the patriarchal and asymmetric ideological vision consolidated and established the legality, but not the legitimacy, nor the representativeness of the Constitution of 1823 that justified an unjust, exclusive and unequal Republic, which continues to be a challenge for the country and democratic coexistence.